Work Motivation and Discipline’s Impact on Teacher’s Performance - Atmaja, Fitra Puja; Fitria, Happy; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2022)
The goal of this study was to look at the influence of work motivation and work discipline on teacher performance at the State Junior High School in Bayung Lencir District, both partially and concurrently. This study was carried out in the State Junior High School in Bayung Lencir District, Musi Banyuasin Regency, with 192 teachers serving as participants. Questionnaires and documents are used to collect data. Construction and content validity are used in the validity test. Conbach alpha is used in the dependability test. Normality, homogeneity, and linearity tests are used to analyze test requirements. Simple regression and multiple regression approaches were used to evaluate the data. According to the findings of this study, there is a partial or simultaneous effect of motivation and work discipline on teacher performance, as well as a positive association between motivation and discipline on teacher performance.